Simplified analytical determination of the temperature distribution and the load bearing resistance of slim‐floor beams. (13th September 2017) - Braun, Matthias; Zaganelli, Dario; Hanus, Francois; Obiala, Renata; Cajot, Louis‐Guy; Peirce, Anthony
ABSTRACT: This contribution presents an analytical method to determine the distribution of temperature within a steel section integrated into a concrete slab, which is subjected to a time‐dependent heat flux. The method developed is based on an analytical solution of the general heat equation for transient conduction simplified to be usable for the calculation of the load bearing resistance of the slim‐floor beam. This simplified analytical solution is validated by comparison against results obtained from numerical simulations. A possible extension of the developed method to fire protected sections is given.